ANALYSIS OF CITRUS COMPARATIF AND COMPETITIVE ADVANTAGE IN PRODUCTION CENTRE - Apri Laila Sayekti; Lizia Zamzami (Pusbindiklat - LIPI, 2011)
These research objectives are to analyze: (1) cost structure of citrus farming system in central production, (2) Indonesia’s citrus competitiveness. Analysis uses the Policy Analysis Matrix (PAM). The analysis showed that citrusfarming in the district Jember and Sambas financially and economically have profitability and are quite promising.Citrus also has a comparative and competitive advantage and it needs effort to improve the competitiveness.